Restorative Justice Perkara Kecelakaan Lalu Lintas Dalam Upaya Menciptakan Keadilan - Aris Rahmawan; Siti Marwiyah; Bachrul Amiq; Wahyu Prawesthi (Jurnal Ragam Pengabdian, 2026)
The Road Traffic and Transportation Law (UULAJ) states that traffic accidents as one of the criminal cases, the case must receive special attention by all parties, along with the increasing number of accidents so that there are more and more cases and make it difficult for law enforcement officials in handling and fulfilling the rights of victims. Related to this research, normative legal research focuses on the analysis of laws and regulations, court decisions, and legal principles; How is Restorative Justice applied by law enforcement in the settlement of traffic accident criminal cases and is Restorative Justice in handling traffic accident cases (KLL) in accordance with Restorative Justice according to positive Indonesian law? This study shows that restorative justice in traffic accident cases has great potential to create more humane justice and support the principle of fast, simple, and inexpensive justice.